Analysis of The Entry of Cash Receipt Deposit Slips in Improving the Accuracy of Financial Statements - Amnatia R Abdullah; Sukriyanto Gausu; Fadlian Kaluku (Journal of Governance and Global Studies, 2026)
This study aims to analyse the process of entering cash receipt deposit slips into the accounting information system and to identify issues that affect the timeliness and accuracy of recording. The research method used is a qualitative approach with a descriptive-analytical research design. Data were collected through observation, interviews, and documentation of parties directly involved in the cash receipt and recording process. The results indicate that, in general, the Deposit Slip entry procedures follow the established workflow; however, delays and input errors still occur, particularly regarding deposit amounts, account codes, and data completeness. These issues are caused by limited human resources, high transaction volumes, and weak internal controls. The conclusion of this study emphasizes that Deposit Slip data entry is a critical stage in the cash receipt accounting information system that requires procedural improvements, strengthened internal controls, and enhanced human resource competencies to improve the quality of financial reports.